Pheromone chirality of asian palm weevils,Rhynchophorus ferrugineus (Oliv.) andR. vulneratus (Panz.) (Coleoptera: Curculionidae) - Pérez Sánchez, Alice Lorena (1996)
Production of 4-methyl-5-nonanol, and 4-methyl-5-nonanone by two sympatric Asian palm weevils,Rhynchophorus ferrugineus (Oliv.) andR. vulneratus (Panz.) suggested that enantiospecificity of either compound could impart species specificity of pheromone communication. Weevil-produced, racemic 4-methyl-5-nonanol and 4-methyl-5-nonanone and their stereoselectively synthesized optical isomers were subjected to gas chromatographic-electroantennographic detection (GC-EAD) and GC-mass spectrometry (MS) on a chiral Cyclodex-B column. Only theS,S stereoisomer of 4-methyl-5-nonanol was EAD active and was produced by bothR. ferrugineus andR. vulneratus. Production and EAD activity of (S)-4-methyl-5-nonanone exceeded that of its antipode in both weevils. In field experiments in Java. (4S, 5S)-4-methyl-5-nonanol and the stereoisomeric mixture were equally attractive. The 4R,5R stereoisomer was inactive. The corresponding ketone enantiomers neither enhanced nor reduced attraction to (4S,5S)-4-methyl-5-nonanol. Lack of apparent differences betweenR. ferrugineus andR. vulneratus pheromones suggests that synonomy of both weevils should be considered unless other pre- or postzygotic reproductive isolating mechanisms are disclosed in future studies.